PENGARUH SUHU, KELEMBABAN, CURAH HUJAN, KECEPATAN ANGIN DAN TINGKAT PENYINARAN MATAHARI TERHADAP FLUKTUASI ENDEMISITAS MALARIA DI KOTA TERNATE - , Ilham Sahuleka ([Yogyakarta] : Universitas Gadjah Mada, 2011)
Background: Ternate City and South Halmahera Regency in North Moluccas Province is categorized as malaria endemic. Therefore, from 23 â 24 April 2010 the Minister of Health of the Republic of Indonesia announces officialy Malaria Center in Labuha South Halmahera Regency and Ternate City as commemoration of World Malaria Day. Ternate City is an interprovincial transitory port, trade center, and education in North Moluccas Province so it facilitates the transmission of malaria. Objective: This study is to find out the effect of fluctuative climate elements, i.e. temperature, moisture, rainfall, wind speed, and sun light rate on the fluctuation of malaria endemicity in Ternate City. Method: This study used an observational method with a cross-sectional design. It used various data, including Annual Malaria Incidence (AMI), Month Malaria Incidence (MOMI), and climate data from BMKG of 2008, 2009, 2010 (January to November) in Ternate City. Result: The analysis of 2008 temperature r= -0.608 with p= 0.038 in PHC of Ternate City, r= -0.690 with p= 0.013 in PHC of Sulamadaha, humidity r= 0.632 with p= 0.027 in PHC of Siko and wind speed r= -0.612 with p= 0.034 in PHC of Kalumpang. In 2009 the temperature r= -0.640, with p= 0.025 in PHC of Siko, humidity r= - 0.727 with p= 0.007 in PHC of Ternate City, r= -0.653 with p= 0.021 in PHC of Kalumata, r= -0.610 with p= 0.035 in PHC of Siko, r= -0.874 with p= 0.000 in PHC of Sulamadaha, Rainfall with r= -0606 with p= 0037 in PHC of Ternate City, r= -0783 with p= 0.003 in PHC of Siko and solar radiation level with r= 0.596 with p= 0.041 in PHC of Siko. In 2010 temperature r= 0.617 with p= 0.043 in PHC of Ternate City , r= 0.839 with p= 0.001 in PHC of Kalumata, rainfall r= -0.718 with p= 0.013 in PHC of Siko, wind speed r= 0.892 with p= 0.000 in PHC of Ternate City , r= 0.740 with p= 0.009 in PHC of Siko, r= 0.820 with p= 0.002 in PHC of Kalumpang and r= 0.705 with p= 0.015 in PHC of Sulamadaha with significance value p <0.05. Conclusion: There is a significant correlation between the increased fluctuation of malaria endemicity in Ternate City and the increased temperature, moisture, high rainfall, low level of wind speed, and the high rate of solar radiation.